IMPLEMENTATION OF THE COVID-19 HEALTH PROTOCOL IN AL-IKHLAS ISLAMIC KINDERGARTEN BANDUNG CLASS SPATIAL THAT MEETS THE GROUP LEARNING SYSTEM - Titihan Sarihati; valkrisda caresti botha; Melati Sukma Nur Hidayat (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The Covid-19 pendemi affects the entire order of human life, specifically the Indonesian people. The education sector is one sector that is feeling the impact of this pendemi. However, the condition of the arrangement and arrangement of the classroom layout has not implemented the COVID-19 health protocol. The arrangement of furniture that is close together and unorganized circulation makes the risk of virus transmission high. The purpose of the research is to create a classroom layout design that applies the COVID-19 health protocol at the Al-Ikhlas Islamic Kindergarten in Bandung and still supports the group learning sistem. This research is focused on the condition of the class layout and the form of furniture, especially children's study tables after the COVID-19 pendemi. Descriptive qualitative research method begins with understanding the current phenomena and then collects data by conducting observations, interviews, and documentation. This research is expected to be one of the solutions and alternative designs that apply the COVID-19 health protocol and can be applied to other kindergarten schools. Based on the analysis and observations that have been made, it can be concluded that the needs of the Al Ikhlas Islamic Kindergarten is the implementation of the Covid-19 health protocol which was carried out in the design of the Al-Ikhlas Bandung Islamic Kindergarten's classroom layout that meets the group learning system, which can be achieved by considering the aspects of the room user's needs, namely both students and teachers. Keywords: implementation, health protocol, Covid-19, spatial planning, kindergarten.